Triggering receptor expressed on myeloid cells-1 (TREM-1) deficiency augments BAFF production to promote lupus progression. (March 2017) - Liu, Chi-Jui; Tsai, Chang-Youh; Chiang, Ssu-Hsuan; Tang, Shye-Jye; Chen, Nien-Jung; Mak, Tak Wah; Sun, Guang-Huan; Sun, Kuang-Hui
Abstract: Sensing of nucleic acids by pattern recognition receptors is the key for the initiation and development of systemic lupus erythematosus (SLE). Triggering receptor expressed on myeloid cells-1 (TREM-1) is a novel innate immune receptor, which can amplify Toll-like receptor (TLR)-induced inflammatory responses. Although patients with lupus exhibit increased serum levels of soluble TREM-1 (sTREM-1), the role of TREM-1 in SLE remains unknown. In current study, we found serum sTREM-1 levels were significantly increased in lupus patients and positively correlated with disease activity. Additionally, diseased B6. lpr mice had elevated TREM-1 in the serum, spleen, and lymph nodes. To investigate the role of TREM-1 in lupus, we established Trem - 1 −/− . lpr mice. Trem - 1 −/− . lpr mice exhibited lower survival rates and more severe lupus symptoms, including elevated proteinuria, serum anti-dsDNA antibody levels, renal immune complex depositions and lymphocyte subpopulation expansions in both the spleen and lymph nodes. Besides, Trem - 1 −/− . lpr mice expressed higher serum B cell-activating factor (BAFF) levels and lymph node dendritic cells (DCs) were the major source of increased BAFF. Activation of membrane-bound TREM-1 could suppress TLR9-induced BAFF expression in bone marrow-derived DCs of B6. lpr mice. Moreover, levels of sTREM-1, which could act as an antagonist of membrane-bound TREM-1, were positively correlated with levels of BAFF in the sera of lupus patients. Our findings suggest a novel modulatory role of TREM-1 in the pathogenesis of SLE. sTREM-1 production is a useful diagnostic marker and a molecular target for combination therapy of lupus. Highlights: Serum sTREM-1 levels is positively correlated with disease activity of SLE. Deficiency of TREM-1 promotes lupus progression. Activation of membrane-bound TREM-1 suppresses BAFF production in DCs. sTREM-1 production may be used as a diagnostic marker and a therapeutic target for lupus.